Aplikasi Pemandu Wisata Berbasis Android Untuk 10 Wisata Bali Baru - Firdaus, Musnadil; Wiyono, Slamet; Af'idah, Dwi Intan; Hidayattullah, Muhammad Fikri (Politeknik Harapan Bersama, 2024)
Tourism has a very significant role in the Indonesian economy. In 2016, the Indonesian government prioritized 10 tourism destinations as